Size-dependent corrosion behavior of graphene oxide coating - Nurul Huda, Abu Bakar; Ali, Gomaa A. M.; Jamil, Ismail; Algarni, H.; K. F., Chong (Elsevier Ltd., 2019)
Graphene oxide emerges as an effective corrosion resistant coating. However, the influence of graphene oxide sheets size on the corrosion protection remains unclear. In this report, we investigate the effect of different graphene oxide (GO) sheets size in the formation of corrosion resistant coating. We provide valuable input for electrophoretic deposition in which GO sheets in smaller size diffuse faster during deposition to cause more oxygen reduction, thereby forms a coating with higher hydrophobicity, stronger adhesion, and lesser pinholes. Detailed electrochemical impedance analysis shows that the coating formed from GO sheets in smaller size exhibits higher activation energy for water diffusion, causing slower water diffusion rate and lower permeation into the coating. The findings suggest that GO sheets in smaller size produce a reliable coating with excellent corrosion resistance behavior.